Density and activity pattern of Leopardus wiedii and Leopardus pardalis in Sierra Norte of Oaxaca, Mexico - Pérez-Irineo, Gabriela; Santos-Moreno, Antonio; Hernández-Sánchez, Alejandro (THERYA, 2017)
The margay, Leopardus wiedii, and the ocelot, L. pardalis, are sympatric species through their distribution areas. Some studies indicate that L. pardalis exerts a strong influence on other smaller felids. Our goal in this study was to estimate the density and activity patterns of these felid species in two vegetation types at Sierra Norte of Oaxaca, southwestern Mexico. We expected that L. pardalis had a high density relative to other felids due to its ecological plasticity, as well as segregation in the activity pattern between species. We placed camera traps in 22 sites in the semi-evergreen forest and 22 sites in the cloud forest, from July 2014 to June 2015. We estimated density using the Cormack-Jolly-Seber probabilistic model with the program MARK and assessed the degree of activity overlapping between species by the coefficient of overlapping Δ1 in the program R. We recorded low abundance of L. pardalis (8.3 individuals) and a higher abundance of L. wiedii (51.5 individuals). The density of both species was 7.8 individuals /100 km2 and 81 individuals/100 km2, respectively. Both species displayed predominantly nocturnal activity. The overlap coefficient between species in the semi-evergreen forest was high (Δ1 = 0.75, CI = 0.63–0.90). Factors such as differences in vegetation type and the presence of a large number of transient individuals may influence the density of Leopardus. The lower density of L. pardalis and the high conservation status of the cloud forest may contribute to the higher density of L. wiedii in Sierra Norte of Oaxaca. Our results suggested that both species showed a highly overlapping activity pattern, and the activity pattern of the margay is seemingly unaffected by the presence of the ocelot. We provided information about density and activity of medium-sized felids, as well as on the factors that may potentially affect these patterns in mountain tropical forests.